Wireless Network For Strategic Boundary Supervision System - Anu Priya; Sasilatha T. (Bulletin of Electrical Engineering and Informatics, 2017)
The major trouble with national security is "Terrorism" happening in borders. In border areas, regular forces or even satellites cannot monitor accurately intruding. The wireless sensor network scheme gives a possible way to explain this issue. To outline a wireless remote system of estimated sensor motes that contains various installed sensors and a processor to detect and impart an adversary interruption crosswise over a border and war zones. The idea is to distribute many smartdust motes inside an enormous geological region. Every one of these motes shapes a remote system, and one of them will go about as the system organiser that can control the whole system and furthermore goes about as a passage to the outside world. The preferred standpoint with these little motes is that it can be conveyed in a couple of hours by a pair of men or even dropped from an airborne helicopter. Every mote comprises of an assortment of sensors to distinguish every single potential type of interruption.